Preparation method of titanium dioxide pigment with low surface hardness
By performing the chlorination process on rutile titanium dioxide and water-soluble silicate and magnesium salt treatment on rutile titanium dioxide, low surface hardness titanium dioxide pigment was prepared, which solved the wear problem of high hardness in inkjet ink and chemical fiber processing, and achieved the effect of reducing hardness and maintaining performance.
Patent Information
- Application Number
- CN202411685577.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-03-04
AI Technical Summary
Rutile-type titanium dioxide is severely worn by the nozzle and discharge port due to high hardness in inkjet ink and chemical fiber processing, affecting production efficiency and product quality.
The chlorination process is used to prepare rutile titanium dioxide preliminary products, and the titanium dioxide pigment with low surface hardness is formed by deionized water beating, adding water-soluble silicate and magnesium salt solutions, controlling pH, maturation and grinding.
It effectively reduces the surface hardness of titanium dioxide pigment while maintaining its excellent whiteness, hiding and weather resistance, reduces wear of nozzles and discharge ports, and extends the service life of the equipment.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a titanium dioxide pigment with low surface hardness. Background Art
[0002] Titanium dioxide, as a core raw material in the field of fine chemicals, is known as the "king of white pigments" for its excellent physical properties, such as high refractive index, excellent tinting power and hiding power. Titanium dioxide plays a vital role in industrial production from coatings, plastics to papermaking, inks and chemical fibers. Its excellent whiteness and hiding power provide ideal appearance effects for various products and meet the market demand for high-quality white pigments.
[0003] Among the many varieties of titanium dioxide, rutile titanium dioxide has higher hardness and more stable chemical properties. The Mohs hardness of rutile titanium dioxide is 6.5-7.0, and the Mohs hardness of anatase titanium dioxide is 6.0-6.5. Compared with anatase titanium dioxide, rutile titanium dioxide has more outstanding advantages in weather resistance and hiding power. Therefore, rutile titanium dioxide has a wider range of applications in the market. However, it is precisely because of its high hardness that the application of rutile titanium dioxide in specific fields such as inkjet inks and chemical fiber processing is limited. In the inkjet process, the high-hardness titanium dioxide particles will cause serious wear on the inkjet nozzle, resulting in frequent nozzle replacement and increased production costs. Similarly, in chemical fiber processing, rutile titanium dioxide will also wear the chemical fiber discharge port, affecting production efficiency and product quality.
[0004] In order to solve the application problem of rutile titanium dioxide in inkjet ink and chemical fiber processing, the market currently mainly relies on anatase titanium dioxide. Although the application of anatase titanium dioxide in these fields can reduce the wear of nozzles and discharge ports, it has a significant gap with rutile titanium dioxide in terms of weather resistance and hiding power, which to a certain extent restricts the application scope of titanium dioxide. Therefore, how to reduce the hardness of rutile titanium dioxide while maintaining its excellent performance has become a key issue that needs to be solved in the current titanium dioxide research and development field. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a titanium dioxide pigment which can effectively reduce the surface hardness of rutile titanium dioxide while maintaining its excellent whiteness, hiding power and better weather resistance.
[0006] A method for preparing a titanium dioxide pigment with low surface hardness, the specific steps of which are as follows: (1) preparing a rutile titanium dioxide primary product by a chlorination process, using deionized water to slurry the primary product to prepare a titanium dioxide slurry, adjusting the slurry pH value to 10.0-10.5 with an inorganic alkali solution; adding a water-soluble silicate solution as a dispersant in an amount of 0.2-0.3% of SiO2 to TiO2 by weight, aging for 20-40 minutes, and grinding; (2) heating the ground slurry to 50°C to 80°C and maintaining this temperature throughout the coating process; (3) adding water-soluble silicate and water-soluble magnesium salt within 90 to 180 minutes, wherein the amount of water-soluble silicate solution added is 9.0% to 15.0% by weight of SiO2 to TiO2, and the amount of water-soluble magnesium salt solution added is 3.0% to 5.0% by weight of MgO to TiO2, and at the same time, controlling the pH value of the slurry to 8.0 to 11.0 with an inorganic acid solution or an inorganic alkali solution, and aging for 60 to 120 minutes; (4) The slurry matured in step (3) is washed with deionized water at 70° C. to 80° C. until the conductivity of the filter cake is greater than 3000 Ω·cm, and then dried and subjected to steam-powder treatment to obtain a titanium dioxide pigment with low surface hardness.
[0007] Furthermore, in steps (1) and (3), the water-soluble silicate solution is a sodium silicate solution or a potassium silicate solution, and the concentration of the water-soluble silicate is 200 g / L to 250 g / L in terms of SiO2.
[0008] Furthermore, in step (3), the water-soluble magnesium salt solution is at least one of a magnesium sulfate solution and a magnesium chloride solution, and the concentration of the water-soluble magnesium salt solution is 50 g / L to 100 g / L in terms of MgO.
[0009] Furthermore, the inorganic acid solution in step (3) is at least one of hydrochloric acid solution, sulfuric acid solution and nitric acid solution, and the mass concentration of the inorganic acid solution is 10% to 20%.
[0010] Furthermore, in step (1), the inorganic alkali solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the mass concentration of the inorganic alkali solution is 20% to 30%.
[0011] Furthermore, in step (3), the mass ratio of the silicon oxide and magnesium oxide coating layer is: SiO2:MgO=3:1.
[0012] Furthermore, the mass concentration of the titanium dioxide slurry in step (1) is 20% to 30%.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The primary product of rutile titanium dioxide produced by the chloride process is used as the raw material, and its particles have the characteristics of a high proportion of spherical particles, a good average particle size and particle size distribution. This optimized particle size distribution helps to improve the key properties of whiteness, hiding power and weather resistance of the final product.
[0014] (2) By introducing a layer of low-hardness magnesium silicate inorganic compound on the surface of titanium dioxide, the film layer has a large porosity. In addition to ensuring that the product has high dry hiding and excellent weather resistance, it can also mainly reduce the hardness of the titanium dioxide surface.
[0015] (3) The magnesium silicate coating not only reduces the hardness, but also blocks the photochemical active points on the surface of titanium dioxide, thereby significantly improving the weather resistance of the product. When the coated titanium dioxide is used outdoors or in harsh environments, the product can maintain color stability and physical properties for a longer period of time.
[0016] This product can be widely used in chemical fiber, inkjet ink and other fields, reducing the wear of inkjet ink nozzles and chemical fiber discharge ports during the production process, extending the service life of the equipment and reducing maintenance production costs. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with specific implementation methods, but the application scope of the present invention is not limited to the embodiments. Various replacements and changes made without departing from the technical idea of the present invention should all be within the scope of the present invention.
[0018] Example 1 1.1. Weigh 400 g of primary rutile titanium dioxide powder prepared by the chlorination method, add deionized water to prepare a slurry with a mass concentration of 20%. The pH value of the slurry is detected by a pH meter during the entire coating process. The pH of the slurry is adjusted to 10.0 with a sodium hydroxide solution with a mass concentration of 20%. A sodium silicate solution is added. The concentration of the sodium silicate solution is 200 g / L in terms of SiO2. The amount of sodium silicate solution added is 0.2% by weight of SiO2 in the sodium silicate to TiO2. The mixture is aged for 20 minutes and ground. 1.2. Heat the ground slurry to 50°C and maintain this temperature throughout the coating process; 1.3. Add sodium silicate solution and magnesium sulfate solution within 90 minutes, the amount of sodium silicate solution added is 9.0% by weight of SiO2 to TiO2, and the concentration of sodium silicate solution is 200g / L based on SiO2; the amount of magnesium sulfate solution added is 3.0% by weight of MgO to TiO2, and the concentration of magnesium sulfate solution is 50g / L based on MgO. At the same time, use a hydrochloric acid solution with a mass concentration of 10% to control the pH value of the slurry to 8.0, and mature for 60 minutes; 1.4. The slurry matured in step 1.3 is washed with deionized water at 70° C. until the filter cake resistivity reaches 3100 Ω·cm. The slurry is filtered, dried, and then subjected to steam-powder treatment to obtain a titanium dioxide pigment with low surface hardness.
[0019] Example 2 1.1. Weigh 400 g of primary rutile titanium dioxide powder prepared by the chlorination method, add deionized water to prepare a slurry with a mass concentration of 30%. The pH value of the slurry is detected by a pH meter during the entire coating process. The pH of the slurry is adjusted to 10.5 with a potassium hydroxide solution with a mass concentration of 30%. Potassium silicate solution is added. The concentration of the potassium silicate solution is 250 g / L in terms of SiO2. The amount of potassium silicate solution added is 0.3% by weight of SiO2 in potassium silicate to TiO2. Ripen for 40 minutes and grind. 1.2. Heat the ground slurry to 80°C and maintain this temperature throughout the coating process; 1.3. Add potassium silicate solution and magnesium chloride solution within 180 minutes, the amount of potassium silicate solution added is 15% by weight of SiO2 to TiO2, the concentration of potassium silicate solution is 250g / L based on SiO2, and the amount of magnesium chloride solution added is 5.0% by weight of MgO to TiO2. At the same time, control the pH value of the slurry to 11.0 with a potassium hydroxide solution with a mass concentration of 30%, and mature for 120 minutes; 1.4. Wash the matured slurry in step 1.3 with 80°C deionized water until the filter cake resistivity is 5500Ω·cm, filter, dry, and then perform steam powder treatment to obtain a titanium dioxide pigment with low surface hardness.
[0020] Example 3 1.1. Weigh 400 g of primary rutile titanium dioxide powder prepared by the chlorination method, add deionized water to prepare a slurry with a mass concentration of 25%. The pH value of the slurry is detected by a pH meter during the entire coating process. The pH of the slurry is adjusted to 10.2 with a sodium hydroxide solution, and a sodium silicate solution is added. The concentration of the sodium silicate solution is 220 g / L in terms of SiO2. The amount of sodium silicate solution added is 0.25% by weight of SiO2 in the sodium silicate to TiO2. Mature for 30 minutes and grind. 1.2. Heat the ground slurry to 65°C and maintain this temperature throughout the coating process; 1.3. Add sodium silicate solution and magnesium chloride solution within 150 minutes, the amount of sodium silicate solution added is 12% by weight of SiO2 to TiO2, the concentration of sodium silicate solution is 220g / L based on SiO2, and the amount of magnesium chloride solution added is 4.0% by weight of MgO to TiO2. At the same time, control the pH value of the slurry to 9.5 with a potassium hydroxide solution with a mass concentration of 25%, and mature for 90 minutes; 1.4. The slurry matured in step 1.3 is washed with 75° C. deionized water until the filter cake resistivity reaches 3800 Ω·cm. The slurry is filtered, dried, and then subjected to steam-powder treatment to obtain a titanium dioxide pigment with low surface hardness.
[0021] Comparative Example 1 Anatase titanium dioxide suitable for use in inkjet and chemical fiber fields is available on the market.
[0022] Comparative Example 2 Weigh 400 g of primary rutile titanium dioxide powder prepared by the chlorination method, add deionized water to prepare a slurry with a mass concentration of 25%, adjust the slurry pH to 9.0 with sodium hydroxide solution, heat to 65° C., mature for 90 min, wash with 75° C. deionized water until the filter cake resistivity is 3800 Ω·cm, filter, dry, and then perform steam powder treatment to obtain rutile titanium dioxide pigment that has not been surface treated.
[0023] Comparative Example 3 1.1. Weigh 400 g of primary rutile titanium dioxide powder prepared by the chlorination method, add deionized water to prepare a slurry with a mass concentration of 25%. The pH value of the slurry is detected by a pH meter during the entire coating process. The pH of the slurry is adjusted to 10.2 with a sodium hydroxide solution, and a sodium silicate solution is added. The concentration of the sodium silicate solution is 220 g / L in terms of SiO2. The amount of sodium silicate solution added is 0.25% by weight of SiO2 in the sodium silicate to TiO2. Mature for 30 minutes and grind. 1.2. Heat the ground slurry to 65°C and maintain this temperature throughout the coating process; 1.3. Add sodium silicate solution and sodium aluminate solution simultaneously within 150 minutes. The amount of sodium silicate solution added is 12% by weight of SiO2 to TiO2, and the amount of sodium aluminate solution added is 4.0% by weight of Al2O3 to TiO2. Use 10% hydrochloric acid solution to maintain the pH value of the slurry at 8.0 and mature for 90 minutes. 1.4. The slurry matured in step 1.3 is washed with 75° C. deionized water until the filter cake resistivity reaches 3800 Ω·cm. The slurry is filtered, dried, and then subjected to steam-powder treatment to obtain a titanium dioxide pigment with low surface hardness.
[0024] Comparative Example 4 1.1. Weigh 400 g of primary rutile titanium dioxide powder prepared by the chlorination method, add deionized water to prepare a slurry with a mass concentration of 25%. The pH value of the slurry is detected by a pH meter during the entire coating process. The pH of the slurry is adjusted to 10.2 with a sodium hydroxide solution, and a sodium silicate solution is added. The concentration of the sodium silicate solution is 220 g / L in terms of SiO2. The amount of sodium silicate solution added is 0.25% by weight of SiO2 in the sodium silicate to TiO2. Mature for 30 minutes and grind. 1.2. Heat the ground slurry to 65°C and maintain this temperature throughout the coating process; 1.3. Add sodium silicate solution and magnesium chloride solution within 150 minutes, the amount of sodium silicate solution added is 6% by weight of SiO2 to TiO2, the concentration of sodium silicate solution is 220g / L based on SiO2, and the amount of magnesium chloride solution added is 2.0% by weight of MgO to TiO2. At the same time, control the pH value of the slurry to 9.5 with a potassium hydroxide solution with a mass concentration of 25%, and mature for 90 minutes; 1.4. Wash the matured slurry in step 1.3 with 75°C deionized water until the filter cake resistivity is 3800Ω·cm, filter, dry, and then perform steam powder treatment to obtain a titanium dioxide pigment with low surface hardness.
[0025] Comparative Example 5 1.1. Weigh 400 g of primary rutile titanium dioxide powder prepared by the chlorination method, add deionized water to prepare a slurry with a mass concentration of 25%. The pH value of the slurry is detected by a pH meter during the entire coating process. The pH of the slurry is adjusted to 10.2 with a sodium hydroxide solution, and a sodium silicate solution is added. The concentration of the sodium silicate solution is 220 g / L in terms of SiO2. The amount of sodium silicate solution added is 0.25% by weight of SiO2 in the sodium silicate to TiO2. Mature for 30 minutes and grind. 1.2. Heat the ground slurry to 65°C and maintain this temperature throughout the coating process; 1.3. Add sodium silicate solution and magnesium chloride solution within 150 minutes, the amount of sodium silicate solution added is 18% by weight of SiO2 to TiO2, the concentration of sodium silicate solution is 220g / L based on SiO2, and the amount of magnesium chloride solution added is 6.0% by weight of MgO to TiO2. At the same time, use a potassium hydroxide solution with a mass concentration of 25% to control the pH value of the slurry to 9.5 and mature for 90 minutes; 1.4. Wash the matured slurry in step 1.3 with 75°C deionized water until the filter cake resistivity is 3800Ω·cm, filter, dry, and then perform steam powder treatment to obtain a titanium dioxide pigment with low surface hardness.
[0026] Comparative Example 6 1.1. Weigh 400 g of primary rutile titanium dioxide powder prepared by the chlorination method, add deionized water to prepare a slurry with a mass concentration of 25%. The pH value of the slurry is detected by a pH meter during the entire coating process. The pH of the slurry is adjusted to 10.2 with a sodium hydroxide solution, and a sodium silicate solution is added. The concentration of the sodium silicate solution is 220 g / L in terms of SiO2. The amount of sodium silicate solution added is 0.25% by weight of SiO2 in the sodium silicate to TiO2. Mature for 30 minutes and grind. 1.2. Heat the ground slurry to 65°C and maintain this temperature throughout the coating process; 1.3. Add sodium silicate solution and magnesium chloride solution within 150 minutes, the amount of sodium silicate solution added is 12% by weight of SiO2 to TiO2, the concentration of sodium silicate solution is 220g / L based on SiO2, and the amount of magnesium chloride solution added is 4.0% by weight of MgO to TiO2. At the same time, control the pH value of the slurry to 7.5 with a potassium hydroxide solution with a mass concentration of 25%, and mature for 90 minutes; 1.4. Wash the matured slurry in step 1.3 with 75°C deionized water until the filter cake resistivity is 3800Ω·cm, filter, dry, and then perform steam powder treatment to obtain a titanium dioxide pigment with low surface hardness.
[0027] Comparative Example 7 1.1. Weigh 400 g of primary rutile titanium dioxide powder prepared by the chlorination method, add deionized water to prepare a slurry with a mass concentration of 25%. The pH value of the slurry is detected by a pH meter during the entire coating process. The pH of the slurry is adjusted to 10.2 with a sodium hydroxide solution, and a sodium silicate solution is added. The concentration of the sodium silicate solution is 220 g / L in terms of SiO2. The amount of sodium silicate solution added is 0.25% by weight of SiO2 in the sodium silicate to TiO2. Mature for 30 minutes and grind. 1.2. Heat the ground slurry to 65°C and maintain this temperature throughout the coating process; 1.3. Add sodium silicate solution and magnesium chloride solution within 150 minutes, the amount of sodium silicate solution added is 12% by weight of SiO2 to TiO2, the concentration of sodium silicate solution is 220g / L based on SiO2, and the amount of magnesium chloride solution added is 4.0% by weight of MgO to TiO2. At the same time, use a potassium hydroxide solution with a mass concentration of 25% to control the pH value of the slurry to 11.5, and mature for 90 minutes; 1.4. The slurry matured in step 1.3 is washed with 75° C. deionized water until the filter cake resistivity reaches 3800 Ω·cm. The slurry is filtered, dried, and then subjected to steam-powder treatment to obtain a titanium dioxide pigment with low surface hardness.
[0028] The titanium dioxide pigments prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested for nanoindentation hardness using a nanoindentation instrument. At the same time, the titanium dioxide pigments prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were mixed evenly with polyester fibers at a total mass of 2% of the titanium dioxide pigment and the polyester fibers, and then injection molded using an injection molding machine to test the sample L* and light transmittance (hiding power). The specific test results are shown in Table 1.
[0029] Table 1 shows the relevant indicators and application indicators of the products in the examples. Serial number Nanoindentation hardness GPa L* Transmittance % (hiding power) Example 1 0.18 94.35 4.52 Example 2 0.12 94.33 4.58 Example 3 0.14 94.38 4.53 Comparative Example 1 0.25 93.65 5.32 Comparative Example 2 0.37 94.36 4.08 Comparative Example 3 0.32 94.28 4.51 Comparative Example 4 0.10 94.10 5.01 Comparative Example 5 0.25 94.37 4.42 Comparative Example 6 0.27 94.34 4.52 Comparative Example 7 0.38 94.35 4.45
[0030] As can be seen from Table 1, the hardness index and application index brightness and light transmittance of the three products of Examples 1 to 3 are very different, meeting the requirements for use in the fields of chemical fiber and inkjet ink.
[0031] The hardness of the anatase titanium dioxide product of Comparative Example 1 is significantly lower than that of the rutile titanium dioxide of Comparative Example 2, but the whiteness and hiding power of the product are significantly lower than those of the rutile titanium dioxide; compared with the rutile titanium dioxide obtained by special surface treatment in Example 3 and the anatase titanium dioxide of Comparative Example 1, the hardness of the anatase titanium dioxide of Comparative Example 1 is higher than that of the rutile titanium dioxide obtained by special surface treatment in Example 3, and the whiteness and hiding power of the anatase titanium dioxide product of Comparative Example 1 are also significantly lower than those of the rutile titanium dioxide obtained by special surface treatment in Example 3. The comparison results of Comparative Example 2 and Example 3 show that after coating in Example 3, the hardness of the product becomes smaller and the hiding power is slightly worse, but it meets the use requirements.
[0032] Compared with the rutile titanium dioxide obtained by special surface treatment in Example 3 and the anatase titanium dioxide in Comparative Example 1, the hardness of the anatase titanium dioxide in Comparative Example 1 is higher than that of the rutile titanium dioxide obtained by special surface treatment in Example 3, and the whiteness and hiding power of the anatase titanium dioxide product in Comparative Example 1 are also significantly lower than those of the rutile titanium dioxide obtained by special surface treatment in Example 3. Comparison of the results of Comparative Example 2 and Example 3 shows that after coating in Example 3, the hardness of the product becomes smaller and the hiding power is slightly worse, but it meets the use requirements. Comparative Example 3 is a parallel test of Example 3. By comparing the results of Example 3 and Comparative Example 3, it can be seen that the surface hardness of the titanium dioxide surface coated with hydrated aluminum silicate in Comparative Example 3 is significantly higher than the surface hardness of the product coated with hydrated magnesium silicate in Example 3. Comparative Example 4 is a parallel test of Example 3. By comparing the results of Example 3 and Comparative Example 4, it can be seen that the amount of magnesium silicate coated on the surface of titanium dioxide in Comparative Example 4 is increased. Although the surface hardness of titanium dioxide is lower, the hiding power of the product is also reduced; and the coating amount is large to a certain extent, the effect of reducing the hardness is not obvious. Comparative Example 5 is a parallel test of Example 3. By comparing the results of Example 3 and Comparative Example 5, it can be seen that the amount of magnesium silicate coated on the surface of titanium dioxide in Comparative Example 5 is reduced, and the surface hardness of titanium dioxide becomes higher. Comparative Example 6 is a parallel test of Example 3. By comparing the results of Example 3 and Comparative Example 6, it can be seen that Comparative Example 6 reduces the pH value of magnesium silicate coated on the surface of titanium dioxide, resulting in a low amount of magnesium silicate coating and a high surface hardness of titanium dioxide. Comparative Example 7 was tested in parallel with Example 3. By comparing the results of Example 3 and Comparative Example 7, it can be seen that Comparative Example 7 increases the pH value of the magnesium silicate coated on the surface of titanium dioxide, resulting in a decrease in the amount of magnesium silicate coated. The surface coating material is mainly magnesium hydroxide and hydrated silicon oxide, and the Mohs hardness of magnesium hydroxide and hydrated silicon oxide is significantly higher than that of magnesium silicate, resulting in a high surface hardness of titanium dioxide.
[0033] It can be seen that the titanium dioxide pigment produced according to the method of the present invention has a low surface hardness while maintaining its excellent whiteness, hiding power and good weather resistance, which can effectively solve the problem that the use of ordinary rutile titanium dioxide in inkjet inks easily causes serious wear of the inkjet nozzle and the use of ordinary titanium dioxide in the chemical fiber field causes serious wear of the extruder head nozzle.
[0034] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a titanium dioxide pigment with low surface hardness, characterized in that: The specific steps are as follows: (1) preparing a rutile titanium dioxide primary product by a chlorination process, using deionized water to slurry the primary product to prepare a titanium dioxide slurry, adjusting the slurry pH value to 10.0-10.5 with an inorganic alkali solution; adding a water-soluble silicate solution as a dispersant in an amount of 0.2-0.3% of SiO2 to TiO2 by weight, aging for 20-40 minutes, and grinding; (2) heating the ground slurry to 50°C to 80°C and maintaining this temperature throughout the coating process; (3) adding water-soluble silicate and water-soluble magnesium salt within 90 to 180 minutes, wherein the amount of water-soluble silicate solution added is 9.0% to 15.0% by weight of SiO2 to TiO2, and the amount of water-soluble magnesium salt solution added is 3.0% to 5.0% by weight of MgO to TiO2, and at the same time, controlling the pH value of the slurry to 8.0 to 11.0 with an inorganic acid solution or an inorganic alkali solution, and aging for 60 to 120 minutes; (4) The slurry matured in step (3) is washed with deionized water at 70° C. to 80° C. until the conductivity of the filter cake is greater than 3000 Ω·cm, and then dried and subjected to steam-powder treatment to obtain a titanium dioxide pigment with low surface hardness.
2. The method for preparing a titanium dioxide pigment with low surface hardness according to claim 1, characterized in that: In steps (1) and (3), the water-soluble silicate solution is a sodium silicate solution or a potassium silicate solution, and the concentration of the water-soluble silicate is 200 g / L to 250 g / L in terms of SiO2.
3. The method for preparing a titanium dioxide pigment with low surface hardness according to claim 1, characterized in that: In step (3), the water-soluble magnesium salt solution is at least one of a magnesium sulfate solution and a magnesium chloride solution, and the concentration of the water-soluble magnesium salt solution is 50 g / L to 100 g / L in terms of MgO.
4. The method for preparing a titanium dioxide pigment with low surface hardness according to claim 1, characterized in that: The inorganic acid solution in step (3) is at least one of hydrochloric acid solution, sulfuric acid solution and nitric acid solution, and the mass concentration of the inorganic acid solution is 10% to 20%.
5. The method for preparing a titanium dioxide pigment with low surface hardness according to claim 1, characterized in that: The inorganic alkali solution in step (1) is at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the mass concentration of the inorganic alkali solution is 20% to 30%.
6. The method for preparing a titanium dioxide pigment with low surface hardness according to claim 1, characterized in that: The mass ratio of silicon oxide and magnesium oxide in the coating layer of step (3) is: SiO2:MgO=3:
1.
7. The method for preparing a titanium dioxide pigment with low surface hardness according to claim 1, characterized in that: The mass concentration of the titanium dioxide slurry in step (1) is 20% to 30%.